2018
DOI: 10.4103/aja.aja_28_18
|View full text |Cite
|
Sign up to set email alerts
|

The corpus cavernosum after treatment with dutasteride or finasteride: A histomorphometric study in a benign prostatic hyperplasia rodent model

Abstract: Erectile dysfunction is a common side effect of finasteride and dutasteride treatments. The objective of this study was to investigate the structural changes in the penis using a benign prostatic hyperplasia (BPH) rodent model treated with dutasteride or finasteride. Sixty male rats were divided into the following groups: C, untreated control rats; C + D, control rats receiving dutasteride; C + F, control rats receiving finasteride; H, untreated spontaneously hypertensive rats (SHRs); H + D, SHRs treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
13
0
3
Order By: Relevance
“…It is well known that the treatment of BPH or alopecia with 5-ARIs may be associated with side effects. These side effects are mainly seen in the penis and characterized by morphological alterations in the corpora cavernosum and transient or permanent erectile disfunction [5][6][7] . However, information regarding side effects in other organs is scarce, especially in tissues not typically recognized as androgen-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that the treatment of BPH or alopecia with 5-ARIs may be associated with side effects. These side effects are mainly seen in the penis and characterized by morphological alterations in the corpora cavernosum and transient or permanent erectile disfunction [5][6][7] . However, information regarding side effects in other organs is scarce, especially in tissues not typically recognized as androgen-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…• Fin (n = 8): received 5 mg/kg/day of finasteride (Finasterida, Eurofarma, São Paulo, SP, Brazil) 5,10,12 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most effective and utilized treatment worldwide is based on 5-alpha-reductase enzyme inhibitors 3,25,28. However, various studies have reported that this treatment generates changes in the morphology of the corpus cavernosum that are linked to erectile dysfunction, after or during therapy 3,72,73…”
Section: Introductionmentioning
confidence: 99%